2008
DOI: 10.1038/embor.2008.222
|View full text |Cite
|
Sign up to set email alerts
|

Neprilysin gene expression requires binding of the amyloid precursor protein intracellular domain to its promoter: implications for Alzheimer disease

Abstract: Amyloid b-peptide (Ab) accumulation leads to neurodegeneration and Alzheimer disease; however, amyloid metabolism is a dynamic process and enzymic mechanisms exist for Ab removal. Considerable controversy surrounds whether the intracellular domain of the amyloid precursor protein (AICD) regulates expression of the Ab-degrading metalloprotease, neprilysin (NEP). By comparing two neuroblastoma cell lines differing substantially in NEP expression, we show by chromatin immunoprecipitation (ChIP) that AICD is bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
159
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 31 publications
11
159
1
Order By: Relevance
“…According to the manufacturer, the specificity of the Silencer select siRNAs was validated by TaqMan gene expression assays. Specific knockdown of APP by Silencer select siRNA has been shown previously (28). After 48 h, cell lysates and media were collected and analyzed using the protocol for cell lysis described above.…”
Section: Methodsmentioning
confidence: 99%
“…According to the manufacturer, the specificity of the Silencer select siRNAs was validated by TaqMan gene expression assays. Specific knockdown of APP by Silencer select siRNA has been shown previously (28). After 48 h, cell lysates and media were collected and analyzed using the protocol for cell lysis described above.…”
Section: Methodsmentioning
confidence: 99%
“…p53 was shown to regulate PrP C at the transcriptional level by interacting with its promoter, resulting in changes in PrP C mRNA and protein expression. Previous work by the same authors 35 and others 36 has reported that the AICD acts as a transcription factor and that one of its target genes is the Aβ-degrading enzyme neprilysin.…”
Section: P53-dependent Transcriptional Control Of Prp C By Presenilinsmentioning
confidence: 99%
“…In other studies to identify AICD-regulated genes, however, the binding of AICD to regulatory cis-elements has only been demonstrated for a limited set of genes. The targets that have been reported to be up-regulated included the metastasis suppressor KAI1/CD82 (60,61), the tumor suppressor TP53 (62), the A␤-degrading enzyme neprilysin (NEP) (42,(62)(63)(64), the endoplasmic reticulum stress and unfolded protein response gene CHOP/DDIT3 (C/EBP homologous protein/ DNA damage-inducible transcript 3) (65), and sonic hedgehog receptor Patched (PTCH1) (66). In contrast, down-regulated targets included the epidermal growth factor receptor (EGFR) (67) and the low density lipoprotein receptorrelated protein 1 (LRP1) (68).…”
Section: Aicd A␤42 and Tau Interactions With Dnamentioning
confidence: 99%